Evaluation of Peak Ground Acceleration Using CPT Data for Liquefaction Potential - Agus Setyo Muntohar (Tsunami Disaster Mitigation Research Center, 2009)
The Universitas Muhammadiyah Yogyakarta (UMY) campus was constructed on 28 hectare which mostly rested on a sand deposit. The ground water table was shallow. Theoretically, the site was susceptible to liquefaction during ground-shaking. During earthquake on May 27, 2006, a magnitude 6.3 shocked the provinces of Yogyakarta, among those number of seismic damages were reported. The damages were identified because of liquefaction phenomena during the ground vibration. Reconnaissance study after the earthquake was found some sand boiling sites near the Masjid and Library building. This paper presents a liquefaction evaluation at those two building. The liquefaction analysis based upon force equilibrium concept can not be directly performed in this study, because there are no accelerometers in the hazard areas in this earthquake. Therefore, the accelerations back-calculated by liquefaction analysis are recommended in this article. The analysis was calculated using 475 cone penetration test (CPT) data that collected from 18 testing sites. By using the CPT data and the estimated cyclic stress ratio from Robertson & Campanella (1985), the critical accelerations from 0.23 g to 0.93 g will generate liquefactions in all depth, loose sand layers in hazard areas. In addition, the accelerations from 0.23g to 0.54g will make 50% of top sand layer liquefied. In general, the estimated ground acceleration of 0.36 g to 0.68 g was sufficient to generate liquefaction at the observed hazard area.